FAKOR-FAKTOR YANG MEMPENGARUHI PROKRASTINASI AKADEMIK PADA MAHASISWA FAKULTAS PSIKOLOGI UIN SUNAN GUNUNG DJATI BANDUNG - Hana Hanifah Fauziah (Psympathic : Jurnal Ilmiah Psikologi, 2015)
The aim of this study was to determine the factors that influence academic procrastination among student as well as make the measuring instrument for academic procrastination. The research method was mixed method with exploratory sequential design. The study was conducted at the Faculty of Psychology UIN Sunan Gunung Jati Bandung with the number of respondents was 113 subjects chosen by disproportionate stratified random sampling. Technical analysis of qualitative data using interactive models while quantitative data using lisrel item analysis to confirm which factors have strong correlation with academic procrastination. The results obtained there were three factors that cause procrastination: physical, psychological, and environmental, with a correlation value for confirmatory analysis as follows 0.50 for the physical aspect, 0.55 for psychological aspects and environmental aspects with 0.92.